ALIH WAHANA RELIEF CERITA BINATANG DI CANDI SOJIWAN KE DALAM FILM ANIMASI SEBAGAI PENDIDIKAN BUDI PEKERTI BAGI ANAK - Harpawati, Tatik; Sugiharto, Ranang Agung (Acintya, 2020)
ABSTRACTThis research is to create an animation as a vehicle for relief from animal stories, especially goats and elephants in Sojiwan Temple to be applied as character education for children. The animation model based on the reliefs of animal stories at Sojiwan Temple is useful for reviving story reliefs that are not recognized by children as local wisdom of the nation's culture. By transforming animal story reliefs into animation, it is hoped that the message of character education can be disseminated to the younger generation.Methods of creation and presentation: (1) exploration of ideas and ideas for creating animated creations based on relief of animal stories; (2) designing a model to find an animation design with a transfer approach; and (3) presenting the results of creating animated characters to facilitate the delivery of character education messages for children to strengthen the character of the younger generation. The results of this study indicate that 1) the reliefs of Sojiwan Temple are mostly in the form of potential animals to be used as references for animation creations and are loaded with good moral values for children's education; 2) the design of the animated characters of Gaga and Bingo, which originates from the form of an elephant and a goat, looks its uniqueness. Keywords: vehicle transfer, animal relief, animation, character, Sojiwan.  ABSTRAK Penelitian ini untuk menciptakan animasi sebagai alih wahana dari relief cerita binatang khususnya kambing dan gajah di Candi Sojiwan untuk diterapkan sebagai pendidikan budi pekerti bagi anak. Model animasi berbasis relief cerita binatang di Candi Sojiwan bermanfaat untuk menghidupkan kembali relief cerita yang sudah tidak dikenali oleh anak-anak sebagai kearifan lokal budaya bangsa. Dengan mengalihwahanakan relief cerita binatang ke dalam bentuk animasi maka pesan pendidikan budi pekerti diharapkan dapat didesiminasikan kepada generasi muda.Metode penciptaan dan penyajian: (1) eksplorasi ide dan gagasan untuk penciptaan kreasi animasi berbasis relief cerita binatang; (2) perancangan model untuk menemukan desain animasi dengan pendekatan alihwahana; dan (3) penyajian hasil penciptaan karakter animasi guna mempermudah penyampaian pesan pendidikan budi pekerti bagi anak untuk memperkuat karakter generasi muda. Hasil penelitian ini menunjukkan bahwa 1) relief Candi Sojiwan yang mayoritas berbentuk binatang potensial untuk dijadikan referensi bagi kreasi animasi dan sarat dengan nilai moral yang bagus untuk edukasi anak-anak; 2) desain karakter animasi tokoh Gaga dan Bingo yang bersumber dari bentuk gajah dan kambing tampak kekhasannya. Kata kunci: alih wahana, relief binatang, animasi, budi pekerti, Sojiwan.